Global Survey on Telemedicine Utilization for Movement Disorders During the COVID‐19 Pandemic. Issue 10 (17th October 2020) - Hassan, Anhar; Mari, Zoltan; Gatto, Emilia M.; Cardozo, Adriana; Youn, Jinyoung; Okubadejo, Njideka; Bajwa, Jawad A.; Shalash, Ali; Fujioka, Shinsuke; Aldaajani, Zakiyah; Cubo, Esther; ,
ABSTRACT: Background: The COVID‐19 pandemic restricted usual healthcare management for movement‐disorders patients, with a consequent upsurge in telemedicine to bridge the gap. Objective: To assess global telemedicine usage in the context of the pandemic. Methods: The Movement Disorder Society (MDS) Telemedicine Study Group surveyed telemedicine experts from 40 countries across all continents in March–April 2020. Four domains of telemedicine were assessed: legal regulations, reimbursement, clinical use, and barriers; comparing emerging responses to the pandemic versus the baseline scenario. Results: All forms of telemedicine for movement disorders increased globally, irrespective of country income categorization, as an immediate response to the pandemic. This was aided by widespread availability of technology and updated government regulations. However, privacy concerns, lack of reimbursement, limited access, and lack of telemedicine training were barriers highlighted worldwide. Conclusions: Questions remain about the longevity and extent of changes in regulations and reimbursement regarding telemedicine in the aftermath of the pandemic. © 2020 International Parkinson and Movement Disorder Society